An Efficient Implementation of the Sign LMS Algorithm Using Block Floating Point Format. (2007) - Chakraborty Chakraborty, Mrityunjoy Mrityunjoy; Shaik Shaik, Rafiahamed Rafiahamed; Lee Lee, Moon Ho Moon Ho
Abstract : An efficient scheme is presented for implementing the sign LMS algorithm in block floating point format, which permits processing of data over a wide dynamic range at a processor complexity and cost as low as that of a fixed point processor. The proposed scheme adopts appropriate formats for representing the filter coefficients and the data. It also employs a scaled representation for the step-size that has a time-varying mantissa and also a time-varying exponent. Using these and an upper bound on the step-size mantissa, update relations for the filter weight mantissas and exponent are developed, taking care so that neither overflow occurs, nor are quantities which are already very small multiplied directly. Separate update relations are also worked out for the step size mantissa. The proposed scheme employs mostly fixed-point-based operations, and thus achieves considerable speedup over its floating-point-based counterpart.